Mild Ovarian Stimulation has Similar Live Birth Rates as Compared with Hyper Stimulation for Treatment of Poor Responding IVF Patients of Advanced Maternal Age - Yang, Pan; Li, Jian-Jun; Wang, Wei-Hua (Journal of Fertility Biomarkers, 2017)
The number of patients with poor ovarian response (POR) for in vitro fertilization (IVF) varies from 9 to 25%, especially high in patients of advanced maternal age. Although various stimulation protocols have been developed to improve clinical outcomes in patients with POR, a typical and effective protocol remains improvement. Some physicians prefer a mild stimulation protocol, while others like hyper stimulation protocol to obtain more eggs. This study was designed to compare the efficiency of a mild stimulation protocol with hyper stimulation protocol in patients with POR, particularly focused on live birth rate after IVF. Data were collected from 30 poor responders (over 39 years old). Patients were assigned to 2 protocols at the start of ovarian stimulation: Patients in group A were treated with a hyper stimulation (GnRH-antagonist) protocol and patients in group B were treated with a mild stimulation protocol. The ovarian stimulation characteristics, gonadotropin doses, number of eggs collected, number of high quality embryos, clinical pregnancy rates and live birth rates were compared between two groups.Although number of eggs, number of high quality embryos, clinical pregnancy rates were significantly higher in group A than in group B, miscarriage rate was also higher in group A than group B, which eventually resulted in a similar live birth rate (6.7%) in both groups. However, dosages of gonadotropins were smaller and stimulation days were shorter in group B than in group A. When poorly responding patients were treated for IVF, similar live birth rates were observed with mild stimulation protocol and hyper-stimulation protocol. After considering the higher dosages of gonadotropins and longer stimulation days in patients with hyper-stimulation protocol, it is suggested that poor responders may benefit with the mild stimulation protocol for IVF.
Keywords: Mild stimulation; Infertility; IVF; Poor ovarian response